Elections and Democracy after Communism? - Herron, E. author. aut Link
XVI, 238 p.
Keywords: This book uses elections as a vehicle to explain the unanticipated outcomes of post-Soviet politics. It assesses how the behavior of voters, candidates and government officials is influenced by the Soviet legacy and rational calculations of self-interest and is the first to address elections across post-Soviet space.